URGENSI ZISWAF DALAM PENGEMBANGAN PEREKONOMIAN DI INDONESIA - Nur Amelia; Rahmawati Rahmawati; Lismawati Lismawati; Rifqil Khairi; Zubaidah Assyifa (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2023)
This article discusses the role of Zakat, Infaq and Alms (Ziswaf) in microeconomic development in This article discusses the role of Zakat, Infaq and Alms (Ziswaf) in microeconomic development in Indonesia. The author explains Ziswaf's urgency in empowering small communities, especially those in the lower economic strata. Funds collected from zakat, infaq and alms can be allocated to support micro and small businesses, provide business capital, and provide training and mentoring to improve the skills and capacity of micro communities. The research method applied is the literature research method or literature review, which is focused on the analysis and synthesis of written works that are relevant to the research topic. The research results show that increasing ZISWAF fund collection has a positive impact on social religious life, poverty alleviation, equitable development, human development, and economic growth. If managed optimally, the existence of ZISWAF will provide a significant boost to economic growth. Therefore, it is emphasized that the government needs to provide greater support to exploit the potential of the ZISWAF instrument in Indonesia.